Prolapsed and incarcerated rectal lipoma: case report and literature review - Liz, Alejandra; Castro, Álvaro; Escuder Rébori, Juan; Viola Malet, Marcelo (Cirugía del Uruguay, 2023)
Colonic lipomas are infrequent benign tumors, extremely rare at the rectum. Nevertheless, they follow in frequency polyp adenomas. Even though most colorectal lipomas are asymptomatic and incidental, they can occasionally be symptomatic and develop acute complications that require urgent surgical treatment. This form of presentation can be confounded with colorectal cancer, therefore impairing diagnosis and treatment. We present the case of a female patient who came to the emergency room with an acute painful mass through the anus, that resulted in a prolapsed rectal lipoma.